The Influence of Teachers’ Performance in Promoting Effective English Teaching Classroom at State Junior High School - Amrina Rosyada; Agustina Ramadhianti (UICELL, 2017)
Promoting effective English teaching classroom is one of the teachers’ concerns which is positive classroom environment for the sake of achieving success in English teaching and learning process. Beyond the presence of the advanced technology and information, teacher’s performance is still the main variable in promoting the effective English teaching classroom. Thus, the research aims at determining the influence of teacher’s performance to promote the effective English teaching classroom in state junior high school. The teacher’s performance focuses in teacher’s personality and teacher’s language. The effective English teaching classroom is measured quantitatively by applying correlational research design. The method conducts several steps as procedures of investigation in analyzing the data, namely: 1) data collection, 2) data analysis, and 3) data interpretation. Engaged by 71 students of eighth grade and 2 English teachers, findings have shown that there is a significant correlation between teacher’s performance and effective English teaching classroom. The results are hoped to be as teachers’ and students’ contributions in establishing their effective English teaching classroom; gaining their confidence and ability to learn; and use knowledge and skills to interact and to fully participate in education.